Physical activity prevents tumor metastasis through modulation of immune function - Zheng, Aiping; Zhang, Lei; Yang, Jiaqing; Yin, Xiaomeng; Zhang, Tao; Wu, Xin; Ma, Xuelei (Frontiers in Pharmacology, 2022)
Metastasis is responsible for 90% of deaths in cancer patients. Most patients diagnosed with metastatic cancer will die within 5 years. PA is good for health and has become an emerging adjuvant therapy for cancer survivors. Regular moderate exercise substantially lowers the incidence and recurrence of several cancers, alleviates cancer-related adverse events, enhances the efficacy of anti-cancer treatments, and improves the quality of life of cancer patients. Revealing the mechanisms of PA inhibiting tumor metastasis could upgrade our understanding of cancer biology and help researchers explore new therapeutic strategies to improve survival in cancer patients. However, it remains poorly understood how physical activity prevents metastasis by modulating tumor behavior. The immune system is involved in each step of tumor metastasis. From invasion to colonization, immune cells interact with tumor cells to secret cytokines and proteases to remodel the tumor microenvironment. Substantial studies demonstrated the ability of physical activity to induce antitumor effects of immune cells. This provides the possibility that physical activity can modulate immune cells behavior to attenuate tumor metastasis. The purpose of this review is to discuss and summarize the critical link between immune function and exercise in metastasis prevention.